2019
DOI: 10.7759/cureus.5442
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Hemophilia A: A Rare but Potentially Fatal Bleeding Disorder

Abstract: Acquired hemophilia A is a disorder of rare entity, resulting in spontaneous bleeding in individuals with no history of bleeding disorders. It is believed to be caused by spontaneous inhibition of clotting factor VIII by autoantibodies, and is usually associated with other autoimmune conditions. The hallmark of this condition is mucocutaneous bleeding leading to ecchymosis, melena, hematoma or hematuria. Our discussion revolves around the case of an elderly male with no history of anticoagulant use presenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 14 publications
1
12
0
5
Order By: Relevance
“…In most cases, autoantibodies are formed against factor VIII, which is known as acquired haemophilia A (2). But in our case, inhibitors were present against both factor VIII and IX, which has the incidence as 1 per million per year, with many cases being undiagnosed (5).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In most cases, autoantibodies are formed against factor VIII, which is known as acquired haemophilia A (2). But in our case, inhibitors were present against both factor VIII and IX, which has the incidence as 1 per million per year, with many cases being undiagnosed (5).…”
Section: Discussionmentioning
confidence: 48%
“…Acquired haemophilia is a haematological disorder caused by the formation of antibodies commonly against factor VIII and rarely against factor IX and other clotting factors. It is a rare bleeding disorder common in the elderly, where the commonest presentation is spontaneous bleeding (5). In most cases, autoantibodies are formed against factor VIII, which is known as acquired haemophilia A (2).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that the bleeding symptoms in AHA are usually severe, physicians should also be aware that mild bleeding can also occur in AHA [9,16,41]. A thorough laboratory examination must be performed to [2,6,12,16].…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Most patients with F8 autoantibodies have hemorrhages in the skin, muscles, or soft tissues and mucous membranes, whereas hemarthrosis, a typical feature of congenital F8 deficiency, is uncommon. This disease develops during a person's lifetime, usually in special conditions, such as pregnancy, after major surgery or very often linked to underlying malignancy, and it is described as an autoimmune disease (40,41). In acquired hemophilia, the newly developed antibodies are different from the alloantibodies developed as a response to rF8 treatment in congenital HA (39) (Figure 1).…”
Section: Aha-a Recently Described Ha With a Non-mutational Backgroundmentioning
confidence: 99%